Fibrinogen Concentrate in Obstetric Hemorrhage - Tavares Ferreira, Cátia Sofia; Alves, Cláudia; Carvalhas, Joana (Journal of the Portuguese Society of Anesthesiology, 2019)
Fibrinogen is a soluble plasmatic glycoprotein. Synthesized in hepatocytes and stored in platelets, it has a plasma concentration between 2-4,5 g/L, increasing in pregnancy, and a half-life of 4-7 days. It functions as an acute phase reactant and is determinant for an effective hemostasis. In hypofibrinogenemia, congenital or acquired, there are three possible approaches for the fill in of fibrinogen: fresh frozen plasma, cryoprecipitate and fibrinogen concentrate. Fibrinogen concentrate has been used to control coagulopathy, contributing to lower the use of allogeneic blood products in major bleeding in various clinical settings. It is an important and effective hemostatic intervention, being considered a "potential universal hemostatic agent". During pregnancy, marked changes in hemostasis are observed disposing to hypercoagulability, a physiological preparation for blood loss at birth. However these also facilitate thromboembolic events. Obstetric hemorrhage is the leading cause of maternal morbidity and mortality, even in developed countries, and is the most preventable cause of mortality. Postpartum hemorrhage is the most common form. Massive hemorrhage in obstetrics is a critical event that requires an assertive interdisciplinary approach. The implementation of obstetric hemorrhage management protocols, with transfusion algorithms, has led to reduction of morbidity, and should exist in all Obstetric Units. The various protocols differ in the hemostatic resuscitation strategy. Decreased plasma fibrinogen levels appear to be a biomarker in predicting increased postpartum hemorrhage, so administration of fibrinogen concentrate is a key hemostatic intervention. There is still no consensus regarding trigger and plasma targeting for fibrinogen replacement. The Portuguese Recommendations of the Portuguese Society of Anesthesiology of 2018 consider hypofibrinogenemia in postpartum hemorrhage when: 1) fibrinogen ≤2.9 g/L; 2) FIBTEM maximum clot firmness ≤18 mm; 3) blood loss ≥1.5 L with continuous bleeding and laboratory results not yet available. They also recommend an initial dose of 25-50 mg/kg, with additional doses pending on clinical evolution and/or laboratory monitoring. The increased use of fibrinogen concentrate, associated with pointof-care coagulation tests, significantly modified the therapeutic strategy in obstetric hemorrhage. Early and targeted correction of coagulopathy is associated with reduction of transfused blood components and related complications. Despite the unquestionable role of fibrinogen concentrate, some issues remain to be defined in order to provide a more precise treatment of obstetric hemorrhage